Brucella endocarditis of bicuspid aortic valve - Sujata Devi; Nilanjan Kar; Debananda Sahoo; Tutan Das; Debasis Acharya; Debasish Das (Journal of Clinical and Preventive Cardiology, 2021)
We present a rare case of Brucella endocarditis in a case of the bicuspid aortic valve in a 51-year-old male presenting with pyrexia of unknown origin for the last 2 months. Infective endocarditis caused by Brucella melitensis is rare to encounter in routine clinical practice. Although we routinely think of Mycoplasma, Legionella, and Coxiella in the cases of blood culture-negative endocarditis, one should think of Brucella melitensis and Scrub typhus as the last arrow to reach the final etiology of infective endocarditis in the subset of diseased aortic or mitral valve. We successfully treated the patient with a combined regimen of rifampicin, gentamicin, and doxycycline therapy; during follow-up, the vegetation of the aortic valve was shrunken and calcified and the patient was asymptomatic.